Exploring The Impact Of Service Quality On BPJS Patient Satisfaction In Hospitals: A Scoping Review - Widyastuti, Indri; Hamidah, Rif'atul; Kusumawati, Silvia Dewi; Ratnawati, Ratnawati (Management Science Research Journal, 2024)
One of the key initiatives to regulate the healthcare system in Indonesia is the establishment of the National Health System, implemented through the BPJS program. Previous research has investigated the impact of healthcare service quality in hospitals on patient satisfaction among BPJS participants. This scoping review aims to map existing research on the relationship between service quality and BPJS patient satisfaction in hospitals. The stages of a scoping review consist of (1) Formulating the research question; (2) Identifying relevant literature; (3) Selecting studies; (4) Mapping the data; and (5) Summarizing, synthesizing, and reporting the results. The studies included in this review cover eight years from 2015 to 2023. The results indicate that all dimensions of service quality significantly influence patient satisfaction (Lahdji et al., 2015; Mukaromah et al., 2022; Natassa & Dwijayanti, 2019; Putri et al., 2016; Tridiyawati & Prahasta, 2022). However, as highlighted by Amalia et al. (2023), Fajri (2016), Pramita et al. (2019), Rahmadani et al. (2021), and Widyastuti et al. (2018), certain dimensions of service quality have a notable impact on patient satisfaction, while others do not.